Implementasi Program Aksi Bergizi dalam Pencegahan Anemia pada Santriwati di Pondok Pesantren Kabupaten Kediri - Siti Komariyah; Byba Melda Suhita; Reni Yuli Astutik; Shanty Natalia; Agustin Widowati; Elfi Quyumi (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Anemia among adolescent girls continues to be a significant public health concern with long-term consequences for reproductive health, productivity, and human resource quality. Poor dietary quality, skipping breakfast, low physical activity, and poor adherence to iron tablet supplementation are key contributing factors. Objective: The Aksi Bergizi Program was developed as a promotive and preventive strategy to improve adolescents’ nutritional behaviors through school- and boarding school-based interventions. Methods: This community service activity applied an educational and participatory approach in a boarding school setting, involving 150 adolescent girls at Boarding School Kediri Regency. The program was implemented from June to July 2025 through an integrated Aksi Bergizi package consisting of nutrition and anemia education, group physical activity, communal breakfast, and collective iron tablet (TTD) consumption. Program evaluation was conducted through observation and descriptive assessment of anemia prevention behaviors. Results: The findings showed that 56% of participants demonstrated positive anemia prevention behaviors. The implementation of group physical activity was categorized as good in 83.3% of participants, communal breakfast in 70%, collective iron tablet consumption in 87.3%, and nutrition and anemia education in 67.3%. Collective iron tablet consumption was the component with the highest level of participation. Conclusion: The Aksi Bergizi Program was effective in improving anemia prevention behaviors among adolescent girls in an Islamic boarding school setting. A collaborative and collective behavior-building approach supports program sustainability and highlights the potential of Aksi Bergizi as a community-based strategy to improve adolescent nutritional status and prevent anemia.